The Role of Anterior Segment Optical Coherence Tomography in Glaucoma - Sarwat Salim (Journal of Ophthalmology)
The anterior segment optical coherence tomography provides an objective method to assess the anterior segment of the eye, including the anatomy of the anterior chamber angle. This technology allows both qualitative and quantitative analyses of the angle and has shown potential in detecting and managing angle-closure glaucoma. In addition, it has a role in identifying pathology in some forms of secondary open-angle glaucoma and postsurgical management of glaucoma. Limitations of this technology include its cost and inability to visualize well structures posterior to the iris, such as the ciliary body. This paper focuses on potential benefits and limitations of anterior segment optical coherence tomography when compared with conventional gonioscopy and ultrasound biomicroscopy. Various clinical entities will be described to discuss its potential role in glaucoma practice.